Application of Spectroscopic Techniques for Antioxidant Property Analysis of Various Food Supplements and Ganoderma lucidum Coffee - Aygun, Zeynep (Biological Sciences - PJSIR, 2017)
In the present study, different methods were used to investigate the magnetic and structural properties of some food supplements and a kind of Ganoderma lucidum coffee. In order to understand the antioxidant capability of the samples and to detect paramagnetic centres, EPR (Electron Paramagnetic Resonance) experiment was carried out at room temperature. To examine the structural features and crystalline property of the samples, XRD (X-ray diffraction) method was used. SEM (Scanning Electron Microscopy) technique was preferred to analyse the surface morphology. Also, EDS (Energy Dispersive Spectroscopy) was performed to get information about the elemental composition of the samples. Antioxidant potential of these samples were examined in detail which is important to support our body functions.